The relationship between external and internal factors of information system success towards employee performance: A case of Royal Malaysia Custom Department - Abd Zakaria, Zuhdi; Anuar, Herman Shah; Mohamed Udin, Zulkifli (2014)
The purpose of this paper is to review external and internal factors of Information Systems (IS) success towards employee performance.The construct of this paper is based on a comprehensive review of recent literature s on external and internal factors of IS success towards employee performance.Detailed discussions follow is to give implications on policy making, especially to the top management of the Royal Malaysia Custom Department (RMCD).External and internal factors of Information systems success largely contributed to the employee performance in achieving the Key Performance Indicator (KPI) as directed by the top management.The information system implementation in RMCD is very crucial due to its duty to collect the revenue for the country.It is also in line with the approach by all government agencies that tries to improve the public services and efficiency in terms of access to information and transaction services.This paper provides the importance of External and Internal Factors of Information Systems Success towards Employee Performance as well as reviewing latest literatures from the perspectives of sustainability and innovation.